An Enhanced Localization Method for Moving Targets in Coal Mines Based on Witness Nodes - Qingsong Hu; Yishan Ding; Lixin Wu; Can Cao; Shen Zhang (International Journal of Distributed Sensor Networks)
An enhanced localization method based on witness nodes (WitEnLoc) is proposed, in which some sensing nodes are selected as witness nodes to confirm the existence of the target at the site given by the initial localization value and improve the accuracy of the existing localization system. WitEnLoc is primarily comprised of three stages: initial value calculation, target node searching, and search result correction. During the initial value calculation stage, the initial value is obtained using the existing localization system, and witness nodes are determined using the IoT (Internet of Things) control platform. In the target node searching stage, inward and/or outward searches are conducted in order to reduce the scope of each target node. During the search result correction stage, the search results are used to correct the initial value in order to obtain a more accurate final value. The simulation results indicate that the proposed WitEnLoc method can significantly improve the accuracy of the existing localization system.